The foundation and completion of Sultan Haji Ahmad Shah Mosque CENTRIS in Gombak (part I) - Fatah Yasin, Raudlotul Firdaus (Centre for Islamisation (CENTRIS), IIUM, 2024)
To guarantee its success, every institution needs its internal workforce. To address this, Centre for Islamisation (CENTRIS), wherein the Sultan Haji Ahmad Shah (SHAS) Mosque is a part of, was established as the management and advocacy group. Its goals are to offer beneficial programs and more balanced lessons that are in line with the lifestyles of Sejahtera Islam to both public and IIUM circles.